EVALUASI PROSES PEMEKARAN KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2003-2020 - Amelia Eka Handayani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Based on Law no. 23 of 2014, the Regional Government has the authority to expand and organize regions in order to realize the effectiveness of regional government administration in line with the ideals of regional autonomy. The formulation of the problem in this study is how to evaluate the process of expansion of the Tapung District, Kampar Regency in 2003-2020 and how the impact of the evaluation on the expansion process of Tapung District in 2003-2020. This study aims to determine the evaluation of the process of expansion of the Tapung District, Kampar Regency in 2003-2020. This research is a descriptive research with a qualitative approach. This research was conducted in Tapung District. Data collection techniques used are interviews and documentation. The data analysis technique used is descriptive qualitative. The results of this study indicate that the efforts to expand Tapung District have been running for 17 years. However, after the evaluation process, it was found that the expansion effort could not be realized due to several inhibiting factors that existed in the internal Tapung District itself. The author concludes that the effort to expand the Tapung District is feasible to continue, because it has been running as expected and has provided results and benefits for the entire community. Keywords: Evaluation, Expansion, District